Animales de la granja - Colella, Olga (Buenos Aires : Editorial Sigmar, 1992)
Introduce a variety of farm animals.
"Un libro Dorling Kindersley."
Keywords: Domestic animals -- Juvenile literature; Animals -- Juvenile literature; Farm life -- Juvenile literature; Animales domesticos -- Literatura juvenil; Animales -- Literatura juvenil